Development and Validation of a Novel Tool for the Prediction of Clopidogrel Response in Chinese Acute Coronary Syndrome Patients: The GeneFA Score - Hongyi Wu; Hongyi Wu; Xiaoye Li; Juying Qian; Juying Qian; Xin Zhao; Xin Zhao; Yao Yao; Qianzhou Lv; Junbo Ge; Junbo Ge (Frontiers Media S.A., 2022)
Aim: Growing evidence indicated that CYP2C19 genotypes could only explain a fraction of the pharmacodynamic response to clopidogrel, while a number of clinical factors also have contributing roles. Our objective was to develop a new risk score to improve prognostication of ischemic events in Chinese patients treated with clopidogrel.Methods: A new risk score was developed and internally validated in 445 patients with acute coronary syndrome (ACS) undergoing coronary stenting. The final score was named the GeneFA score based on the inclusion of CYP2C19 genotype, fibrinogen, and age. External validation of the GeneFA score and comparison with the ABCD-GENE score were performed in an independent ACS cohort.Results: Based on the observed frequencies of high platelet reactivity (HRPR) in relation to the GeneFA risk score, a relatively higher clinical HRPR was observed in the upper quintile with a representative score of 3 (52.90%) and 4 (59.10%), whereas it was found less frequently in groups with scores 0 (6.70%), 1 (15.10%), and 2 (16.70%). Participants with a GeneFA score >2 had an increased risk of HRPR (54.3 vs. 14.7%, p < 0.001) and ischemic recurrence (20.7 vs. 5.4%, p < 0.001). The GeneFA score exhibited a better prediction for high HRPR patients as compared to the ABCD-GENE score (p < 0.001). In the validation population, GeneFA illustrated a similarly high prognostic value for HRPR incidence (C-statistic: 0.855 for GeneFA and 0.843 for ABCD-GENE) and ischemic recurrence (C-statistic: 0.726 for GeneFA and 0.724 for ABCD-GENE) on clopidogrel as compared to ABCD-GENE.Conclusion: The GeneFA risk score had a moderate predictive ability for HRPR on clopidogrel for CAD patients in Chinese populations. The predictive value of the GeneFA score was consistent with the ABCD-GENE score for HRPR identification.